Diagrams as centerpiece for an enactivist epistemology - Cerutti, Michele (Semiotika, 2023)
In the present work I will examine two semiotic contributions, Legg (2021) and Caravà (2019) respectively, that explore the possible connection between semiotics and enactivism. Both attempt to offer a semiotic interpretation of the enactivist theory of perception and cognition, with the aim of showing how semiotics can contribute to the debate on mental representations. I will argue that Legg’s proposal, based on the Peircean concept of the dicisign, assigns to basic cognition conditions that are not necessary, from the point of view of enactivism. Caravà’s, in turn, assigns non-sufficient conditions. I will argue that if we want to semiotically interpret the enactivist framework the concept that describes necessary and sufficient conditions is that of the diagram.